PENGUATAN LITERASI PUBLIK DALAM ERA MASYARAKAT DIGITAL - Denar, Benediktus (STIPAS TAHASAK DANUM PAMBELUM KEUSKUPAN PALANGKARAYA, 2017)
One of the main factors that support the changing world today is thedevelopment of information and communication technology which isincreasingly sophisticated. In Indonesia, the advancement of informationtechnology has had a significant impact on democracy. This article argues thata dignified democracy requires the quality of public literacy. Good literaturewill bear to citizens who think critically, rationally, constructively, and havethe depth and breadth of insight. The creation of literacy culture should be veryreal in educational institutions, especially in higher education institutions.Without literacy, the world of education is like a soulless body